Interaction between endodontics and periodontics. Issue 1 (21st April 2017) - Rotstein, Ilan
Abstract: Endodontic–periodontal lesions present challenges to the clinician regarding diagnosis, treatment planning and prognosis. Etiologic factors, such as bacteria and viruses, as well as contributing factors, such as trauma, root resorptions, perforations, cracks and dental malformations, play an important role in the development and progression of such lesions. Treatment and prognosis of endodontic–periodontal lesions vary, depending on the etiology, pathogenesis and correct diagnosis of each specific condition. This chapter will appraise the interrelationship between endodontic and periodontal lesions and provide biological and clinical evidence for diagnosis, prognosis and decision‐making in the treatment of these conditions.